2022
DOI: 10.1177/17411432221113683
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between distributed leadership and teacher well-being: The mediating roles of organisational trust

Abstract: Teacher well-being plays an important role in education reform because it marks teachers’ positive evaluation of and healthy functioning in their work environment. However, there has been insufficient research on the relationship between distributed leadership and teacher well-being and on how organisational trust works as a mediator between these two constructs. Based on responses from 587 teachers in primary schools in southwest China, this study examined how distributed leadership contributes to teacher wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…The role of trust has been the focus of research on transformational leadership since change leaders seem to generate more trust . Recent studies have also proved that distributed leadership can positively affect teacher well-being (Liu et al, 2022). In addition, employees tend to follow leaders they can trust and who make them feel secure (Kouzes and Posner, 2017).…”
Section: Trust In Leadersmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of trust has been the focus of research on transformational leadership since change leaders seem to generate more trust . Recent studies have also proved that distributed leadership can positively affect teacher well-being (Liu et al, 2022). In addition, employees tend to follow leaders they can trust and who make them feel secure (Kouzes and Posner, 2017).…”
Section: Trust In Leadersmentioning
confidence: 99%
“…Based on the above discussion, it can be inferred that trust in leaders could mediate the relationship between teacher leadership and teacher well-being theoretically. Research conducted by Liu et al (2022) has suggested that individual trust in colleagues and trust in principals mediates the relationship between distributed leadership and teacher well-being. Other research has shown that good principal-teacher relationships can increase teacher job satisfaction (Torres and Chrispeels, 2022;Van Maele et al, 2014).…”
Section: Trust In Leadersmentioning
confidence: 99%
See 3 more Smart Citations